131k views
2 votes
-3x-6=9x+6 let's if we on the same page

1 Answer

2 votes

Answer:

The solution to the equation is;


x=-1

Step-by-step explanation:

Given the equation;


-3x-6=9x+6

firstly, let us subtract 6 from both sides;


\begin{gathered} -3x-6-6=9x+6-6 \\ -3x-12=9x \end{gathered}

then we can add 3x to both sides;


\begin{gathered} -3x+3x-12=9x+3x \\ -12=12x \end{gathered}

lastly, divide both sides by 12;


\begin{gathered} (-12)/(12)=(12x)/(12) \\ -1=x \\ x=-1 \end{gathered}

Therefore, the solution to the equation is;


x=-1
User Ariel T
by
4.8k points